Exploring mutualistic interactions between microalgae and bacteria in the omics age. (August 2015) - Cooper, Matthew B; Smith, Alison G
Highlights: Microalgae, key primary producers in aquatic ecosystems, interact extensively with bacteria. Metagenomics indicate certain bacterial families are more likely to associate with algae. Compounds exchanged are being identified by functional omics approaches. Evidence is emerging for signalling and regulation of interactions via these compounds. Abstract : Microalgae undertake a wide range of mutualistic interactions with bacteria. Here we consider how transcriptomic, metagenomic and metabolomic approaches have been combined with microbiological and biochemical analyses to expand our understanding of algal–bacterial interactions. Identification of the major bacterial species associated with algae indicates that specific bacterial groups, particularly the alpha-Proteobacteria, are found more frequently, suggesting that these may have the means to initiate and maintain symbiotic relationships. Nutrient exchange is frequently the basis of algal–bacterial mutualism, and as the compounds involved are characterised, evidence is accumulating that these are complex and specific molecules, offering opportunities for signalling processes and regulation rather than merely passive diffusion. At the same time, it is clear that the interactions are not static, but can be initiated and broken in response to environmental and developmental cues.